Recent Developments in Healthcare Through Machine Learning and Artificial Intelligence - Royani, Royani; Maulina, Sondang Deri; Sugiyono, Sugiyono; Anugrah, Rio Wahyudin; Callula, Brigitta (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
This research is a review of recent advancements in the utilization of Machine Learning (ML) and Artificial Intelligence (AI), emphasizing their significant developments across diverse application domains. The purpose of this study is to provide a comprehensive understanding of these technologies and their transformative potential. To achieve this, we conducted an extensive analysis of scholarly literature and case studies, focusing on key applications and recent trends in AI and ML. Our findings reveal critical advancements, particularly in sectors such as business, healthcare, and automation, showcasing the profound impact of these technologies on innovation and operational efficiency. The review also highlights persistent challenges, including ethical concerns, data privacy, and infrastructure requirements. These insights are intended to assist stakeholders in identifying opportunities for the effective implementation and future development of AI and ML applications, ensuring their continued contribution to technological progress.